Development of Interactive Media for Physical Education, Sports, and Health Subjects in Junior High School - Kusuma, Renno Jati; Atrup, Atrup; Pratama, Budiman Agung; Daulay, Dicky Edwar (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
Learning physical education, sports and health at SMP Negeri 3 Wates can be said to be less effective due to several factors. First, the limited availability of textbooks which is one of the students' learning resources. As a result, during physical education lessons, students only do practical activities in the field. The purpose of this study is to determine students' understanding of physical education material, which leads to confusion during written exams. This research and development model of multimedia learning for Physical Education, Sports, and Health for grade VII students in junior high school uses a Research and Development (R&D) approach, using the multimedia development model developed by Borg & Gall. Borg and Gall's research and development process involves 10 steps, of which researchers will apply 9 steps, including: (1) Potential and problems, (2) Data collection, (3) Product design, (4) Design validation, (5) Design revision, (6) Product trial, (7) Design revision, (8) Usage trial, and (9) Product revision. Based on the conclusions of this study, the development of Android-based interactive media is considered valid, with 75% validation from learning experts and 75% validation from media experts, signifying the validation of Android-based interactive media. Android-based interactive media is considered effective for use in learning, because it obtained a percentage of 80% in the limited trial and 86% in the broad trial.